Functional Outcomes of Distal Humerus Fractures in Adults Treated with Precontoured Anatomical Locking Plates in Parallel Fashion: A Study from a Tertiary Centre in India (GAIMS Journal of Medical Sciences, 2023)
Introduction: Distal humerus fractures accounts for 2-6% of all fractures and 1/3 of all humerus fractures. Intra-articular fractures of distal humerus are very rare accounting for 0.5% of all fractures. In the modern society having growing elderly population and an extremely active young population, the incidence of distal humeral fractures is rising and having a bimodal distribution. In young adults, most fractures occur from high-energy trauma like sideswipe injuries, motor vehicle accidents (MVA). In elderly persons with more osteoporotic bone, these injuries occur from simple falls. For fracture fixation two modalities are commonly used they are orthogonal (perpendicular) plate fixation and parallel plate fixation many researchers have reported poor outcomes with perpendicular plate fixation, thus this study aims at analysing the functional outcomes of parallel plates in fixation of distal humerus fracture.Material and Methods: A prospective study was carried out at GAIMS, Bhuj during the period of October 2021 to December 2022. Patients satisfying the inclusion criteria like Age group from 18 years to 65 years and closed distal humerus fractures were included in the study. While open fracture patients, polytrauma patients, patients having neurovascular deficit, patients having pathological fractures and patients unwilling, and medically not fit for surgery were excluded from the study.Results: Out of total 32 patients majority of patients had intra-articular High T type fracture. Male to female ratio was 4:1. Most common age group was 31-40 yrs. Most common mode of injury was road traffic accident. Complications included stiffness, superficial infection, plate impingement, myositis, pain, nerve injury and nonunion at osteotomy site. Mayo Elbow Performance Score (out of 100) in our study was 72 minimum and 94 maximum. The average score was 83. We had excellent results in 10 (32%) patients, 19(58%) had good results, 2(6%) patients had fair results and 1(4%) of the case had poor result.Conclusion: Fixation of distal humerus with dual platting in parallel fashion provides good to excellent results with minimum post-operative complications and good range of motion.